The principles and main directions of development of the mortgage market in modern Russia - V. Busov (Вестник университета)
The article describes the main principles and directions of development of the real estate market in the Russian Federation, providing increase of availability of habitation for the population, improving the efficiency of the system of funding of mortgage transactions in the country. Pay particular attention to trends of improvement of system mortgage lending for construction and purchase of residential property in modern economic conditions of Russia.